THE ANALYSIS OF ELLIPSIS AND SUBSTITUTION OF YOUTUBE ADVERTISEMENTS - Amrin Saragih, Viatari Dipa Pencawan and (LINGUISTICA, 2015)
The study was deal with the types of ellipsis andsubstitution occurred in theutterances of Youtube Advertisements. The objectives of the study was to identify and classify the types of ellipsis and substitution and explaining the reason why it becomes the dominant type that occurred in the advertisement. The data were analyzed by identifying the utterances found in thescript. The findings shows that the three types of ellipsis and substitution are occurred in the advertisement. The reason why it becomes the dominant type was because ellipsis and substitution can make an effective sentence which can be avoid the repetition of words by omitting unnecessary words which can be predicted from the context. It also can make the sentence in the script more interesting.